Pengaruh Pemahaman, Kesadaran, Kualitas Pelayanan dan Ketegasan Sanksi Terhadap Kepatuhan Membayar Pajak Wajib Pajak Orang Pribadi di KPP Pratama Pondok Gede - Lisia Oktafiani; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The purpose of this study was conducted to determine the relationship and influence of understanding, awareness, service quality, and firmness of sanctions on compliance with paying individual taxpayers' taxes at KPP Pratama Pondok Gede. This study uses quantitative data by distributing questionnaires to respondents using a Likert scale. The population is an individual taxpayer who is registered and actively making tax payments. The sample is 100 people with non-probability quota sampling technique. Data analysis methods include: research instrument test, classical assumption test, multiple linear regression test and hypothesis testing. The result of this research is that understanding and service quality have no effect on individual taxpayer compliance. Awareness and firmness of sanctions have a positive and significant impact on individual taxpayer compliance.